SELP+ TEC:CD8+ T cell crosstalk associates with improved radiotherapy efficacy in cervical cancer - Qingyu Huang; Wenhui Yang; Fuhao Wang; Rui Huang; Qian Wang; Xiaohui Li; Tianyu Lei; Shengqin Yue; Wenxue Zou; Qi An; Jinbo Yue; Qinyong Hu; et al. (Molecular Cancer)
Abstract P-selectin (SELP) expression in tumor cells has been implicated in promoting tumor progression and treatment resistance across various cancers. However, our prior study identified SELP expression in a specific subpopulation of endothelial cells within cervical cancer (CC) and potentially linked to anti-cancer immune response. The precise mechanisms by which SELP influences anti-cancer immunity and its involvement in radiotherapy response in CC, however, remain elusive. To address these gaps, this study analyzed tumor tissue samples from 205 CC patients undergoing radiotherapy, scRNA-seq data from 42,159 cells of eight patients, and bulk RNA-sequencing data from 187 radiotherapy-treated patients. The results revealed that elevated SELP expression in tumor endothelial cells (TECs) was significantly correlated with improved survival outcomes in patients treated with radiotherapy. The SELP high group exhibited a prominent enrichment of immune-related pathways, coupled with a diminished enrichment in epithelial cell proliferation and angiogenesis pathways. Notably, this group demonstrated increased infiltration of CD8+ T cells and enhanced expression of chemokine receptors, including ACKR1. Furthermore, our data suggest that SELP+ TECs engage in crosstalk with CD8+ T cells via the ACKR1-CCL5 axis, which is associated with improved radiotherapy efficacy. In conclusion, these findings underscore the pivotal role of SELP+ TEC:CD8+ T cell interactions through the ACKR1-CCL5 pathway in enhancing radiotherapy response in CC. Targeting this crosstalk may offer novel therapeutic strategies to mitigate treatment resistance and improve patient survival.